The Effect of Quizwhizzer Game as Gamification to Motivate and Improve Learning Outcomes of English Learners in Vocational School - Fauzi*, Ahmad; Rachman, Dzul (Universitas Syiah Kuala, 2024)
Motivation plays a crucial role in the student learning process, especially in the context of learning English. Students' success in acquiring language skills is directly influenced by their level of motivation. Low learning motivation can result from monotonous learning techniques that are less effective in stimulating students' enthusiasm for learning, negatively impacting their academic achievement. This research focuses on increasing student learning motivation and outcomes using QuizWhizzer as a gamification tool. The purpose of this study is to investigate how the gamification of learning activities with QuizWhizzer influences students' motivation and learning outcomes in English classes. Using a pretest-posttest design with one group, this research is classified as pre-experimental. High school students from SMKN 15 Samarinda were selected as research subjects using purposive sampling. Questionnaires and tests were employed to collect data on learning motivation and outcomes. The QuizWhizzer program was integrated into learning activities after the pre-test, followed by a post-test and a questionnaire. The results showed a significant increase in both motivation and learning outcomes. The average pretest score increased from 48.12 to 79.62 in the post-test, with an N-Gain of 0.61 classified as medium. The students' learning motivation was also categorized as very high, with an average score of 85.23%. This study provides valuable insights into the effectiveness of gamified learning activities in enhancing students' motivation and academic performance in English.